Faktor-Faktor yang Mempengaruhi Keberhasilan Manajemen Laktasi pada Ibu Bekerja - Putri Damaiyanti; Verawaty Fitrinelda Silaban; Riska Andriani; Rita Rita; Riska Ariani; Purnama Purnama (Universitas Malahayati Lampung, 2025)
ABSTRACT Lactation management refers to a series of actions designed to ensure the entire breastfeeding process is successful, from breast milk production to the baby being able to suck and swallow breast milk properly. The main problem of low rates of exclusive breastfeeding is influenced by several factors including education, knowledge, attitude/behavior, psychological, physical mother, social and cultural, working mothers, and the availability of supporting technology such as breast pumps. This study design uses descriptive analytic with a cross-sectional approach. Researchers used a questionnaire to obtain accurate data. The sampling technique with total sampling is the total number of respondents of 40 respondents. The variables in the study are divided into dependent variables (success of lactation management) with independent variables (work environment support, social support, mother's knowledge and skills, mother's physical and psychological health conditions, and use of supporting technology). The results of the chi-square statistical test obtained showed the influence of work environment support factors (p 0.002), social support factors (p 0.962), mother's knowledge and skills factors (p 0.000), mother's physical and psychological health factors (p 0.006), and use of supporting technology factors (p 0.017). Conclusion: The study states that there is no influence between the success of lactation management and social support factors. However, there is an influence between the success of lactation management and work environment support factors, maternal knowledge and skills factors, maternal physical and psychological health factors and supporting technology factors. Keywords: Succes Factors, Lactation Management, Working Mothers ABSTRAK Manajemen laktasi merujuk pada serangkaian tindakan yang dirancang untuk memastikan keseluruhan proses menyusui berjalan dengan sukses, mulai dari produksi ASI hingga bayi mampu menghisap dan menelan ASI dengan baik. Masalah utama rendahnya tingkat pemberian ASI eksklusif dipengaruhi beberapa faktor diantaranya pendidikan, pengetahuan, sikap/ perilaku, psikologis, fisik ibu, sosial serta budaya, ibu yang bekerja, serta ketersediaan teknologi pendukung seperti pompa ASI. Desain penelitian ini menggunakan deskriptif analitik dengan pendekatan cross sectional. Peneliti menggunakan kuesioner untuk memperoleh data yang akurat. Teknik dalam pengambilan sample dengan total sampling yaitu seluruh jumlah total responden sebesar 40 responden. Variabel dalam penelitian terbagi yaitu variabel dependen (keberhasilan manajemen laktasi) dengan variabel independen (dukungan lingkungan kerja, dukungan sosial, pengetahuan dan keterampilan ibu, kondisi kesehatan fisik dan psikis ibu, serta penggunaan teknologi pendukung). Hasil uji statistic chi-square diperoleh menunjukkan pengaruh faktor dukungan lingkungan kerja (p 0.002), faktor dukungan sosial (p 0.962), faktor pengetahuan dan keterampilan ibu (p 0.000), faktor kesehatan fisik dan psikis ibu (p 0.006), faktor penggunaan teknologi pendukung (p 0.017). Kesimpulan: Penelitian menyatakan bahwa tidak ada pengaruh antara keberhasilan manajemen laktasi dengan faktor dukungan sosial. Namun terdapat pengaruh antara keberhasilan manajemen laktasi dengan faktor dukungan lingkungan kerja, faktor pengetahuan dan keterampilan ibu, faktor kesehatan fisik dan psikis ibu dan faktor teknologi pendukung. Kata Kunci: Faktor-Faktor keberhasilan, Manajemen Laktasi, Ibu Bekerja